Labor market performance in Serbia, Montenegro and Bosnia and Herzegovina from a gender perspective - Radonjić, Ognjen; Jarić, Isidora (Etnoantropološki problemi / Issues in Ethnology and Anthropology, 2015)
In this paper we analyze some aspects of the efficiency of labor markets in Serbia, Montenegro and Bosnia and Herzegovina and compare resulting outcomes with the outcomes of labor markets efficiency in selected economies of the European Union. A particular focus of our analysis is on gender equality, due to the fact that not only gender inequality negatively affects the quality of life of individuals and society in general, but also can produce significant macroeconomic losses which negatively affect economic growth and development. When formulating policy that aims to increase the employability and income of the local population, our recommendation to governments, non-governmental and supranational institutions is to simultaneously take all necessary steps in order to provide women equal access to labor markets. This primarily refers to equality in access to newly created jobs, the uniformity of wages for a work with equal qualification, equal access to employment in formal economy, equal safety at work, equal access to social safety net etc.